REPRESENTASI MASKULINITAS DALAM IKLAN TELEVISI (ANALISIS SEMIOTIKA IKLAN NIVEA MEN ‘BERUBAH EXTRA CERAH’ VERSI ADIPATI DOLKEN) - Fadly Siswoyo; Stara Asrita (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
This research discusses the representation of masculinity in the advertisement of Nivea Men "Changing Extra Bright" and the Adipati Dolken Version of Gatsby Styling Pomade which aims to identify and reveal the meaning of masculinity behind the message. This type of research is qualitative research with Roland Barthes' semiotic model which has core concepts, namely signs, denotations, connotations and myths. The results are masculinity depicted in the two advertisements is divided into two types of masculinity, namely traditional masculinity and new (metrosexual) masculinity. With the myths that were found, namely: (a) Nivea Men 'advertisement' Turns Extra Bright: Self-confidence increases after washing your face and masculinity which is macho. (b) Adipati Dolken version of the Gatsby Styling Pomade: Men today who pay attention to appearance and men with their automotive world. For the analysis of commodification found, namely: (a) Commodification of Content and (b) Commodification of Audiences.